Optimalisasi Undang-Undang Nomor 11 Tahun 2008 Tentang Informasi dan Transaksi Elektronik dalam Penanganan Perkara Tindak Pidana Phising - Septian Arya Budi Mahesa (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Cybercrime in Indonesia is growing rapidly and experiencing extraordinary developments, but this is not accompanied by legal certainty for the protection of personal data for Indonesian people who are currently experiencing various types of attacks on personal data, one of which is phishing. Phishing is a crime committed by sending a link randomly to the victim and if the victim opens the link, personal data theft will occur and result in selling personal data to the dark web or deep web. The Industrial Revolution 4.0 or what is often referred to as the cyber physical system is a revolution that focuses on automation and collaboration between cyber technologies. The 4.0 revolution itself emerged in the 21st century with the main characteristic being the incorporation of information and communication technology into the industrial sector. The method that the researcher uses is normative law, namely a legal literature research based on legal norms in regulations where especially here using Law 11 of 2008 concerning Information and Electronic Transactions.